Turbulenca - Mur, Urban (Matrika, 2016)
The article presents a physical phenomenon in the flow of fluids - the turbulence. After general introduction an elementary introduction of turbulence is presented. Theory of Kolmogorov, which is the basic theory to describe this phenomenon, is addressed. Next the multifractal approach, which is well established, modern approach for a description and understanding of turbulence, is introduced. The second part of the article is dedicated to selected measurements of turbulence, where the use of Doppler effect for measuring the Lagrangian turbulence and use of helium in turbulence experiments is presented.
Keywords: hidrodinamika; hydrodynamics; Kolmogorov theory; measurements; merjenje turbulence; multifractal approach; multifraktalni pristop; teorija Kolmogorova; turbulenca; turbulence